The Effect of Liquidity, Solvency, Activity, and Profitability on Financial Distress in Textile Companies Listed on the Indonesia Stock Exchange - Riska Amelia; Hirdinis Mansyur (International Humanities and Applied Science Journal, 2026)
This study aims to examine the effect of liquidity, solvency, activity, and profitability on financial distress. This research employs a causal research design. The population consists of textile companies listed on the Corporations registered on the Indonesia Stock Exchange during 2015 and 2024 were examined, with five entities chosen through purposive criteria. Panel regression techniques were employed to process the dataset. The findings indicate that liquidity, , solvency, and activity do not exhibit a meaningful influence on financial distress, whereas profitability measured through Return on Assets (ROA) indicates a negative correlation suggesting that increased profitability lowers distress probability. This research enriches academic discourse by offering data-driven findings derived from the Indonesian textile sub-sector using a longer observation period (2015–2024), capturing financial dynamics before, before, throughout, and following the COVID-19 outbreak, as well as offering insights for management and investors in assessing financial conditions. Keywords: Liquidity; Solvency; Activity; Profitability; Financial Distress